KEDUDUKAN PERATURAN MENTERI PADA KONSTITUSI - RUMIARTA, I NYOMAN PRABHU BUANA (Fakultas Hukum Universitas Dwijendra, 2015)
ABSTRACTBased on Article 7 paragraph (1) of Act No. 12 year 2011, states that the type and hierarchy of legislation consists of the Constitution of the Republic of Indonesia year 1945, the People's Consultative Assembly Decree, Laws/Government Regulation in Lieu of Law laws, government regulations, the Presidential Decree, and the Provincial Regulation. Besides laws that have been set out in Article 7 paragraph (1) is, Act No. 12 year 2011 also recognizes other legislation, one regulation. Position regulation established after the enactment of Act No. 12 Year 2011, both established on the basis of the order of legislation that is higher or formed on the basis of authority in the field of government affairs particular that of the minister, qualified as legislation.Â Keywords: Position and Authority, Regulation Legislation, Regulation of the Minister.Â